THE ASSYRIAN DISTANZANGABEN IN RELATION TO THE REGNAL YEARS RECORDED IN THE ASSYRIAN KING LIST. (December 2021) - Mahieu, Bieke
Abstract : Several so-called Distanzangaben (lit. "designations of distance"), found in Assyrian inscriptions, record time spans between events (mainly building activities) of Assyrian rulers. Such chronological data have mostly been studied as entities (for purposes of absolute chronology), and only rarely with regard to their composition. While some of the Distanzangaben can be explained as mere summations of the regnal years recorded in the Assyrian King List, others remain enigmatic. The present article attempts to trace the composition of every Distanzangabe . For those compiled by Tiglath-pileser I and Esarhaddon, ideological purposes seem to be implied. The one compiled by Sennacherib sheds light on the chronology of Tiglath-pileser I's campaigns.